The Level of Recreational Activities Practice among University Professors at the University in Aflou - Douib , Chikh; Elhadj Aissa , Rafik (sports creativity, 2025)
he study aimed to identify the level and differences in the practice of recreational activities according to the age variable among university professors at the University Center in Aflou. A descriptive approach was adopted, with a randomly selected sample of 43 professors (male and female). A pre-designed questionnaire was used as the data collection tool. The study concluded with the following results: The level of participation in recreational activities is high. There are no statistically significant differences in the level of participation in recreational sports activities based on the age variable.